THERMAL PROPERTIES OF POLYMER COMPOSITES REINFORCED WITH FILLERS OF DIFFERENT ELECTRICAL CONDUCTIVITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the thermal properties of polymer composites reinforced with fillers of different electrical conductivity. Since polymers generally have low thermal conductivity, their application in high-temperature processes is limited. Therefore, the possibilities of improving thermal conductivity, thermal stability, and the coefficient of thermal expansion by introducing various fillers (metallic, carbon-based, and dielectric materials) are considered. Metallic and carbon-based fillers enhance both the thermal and electrical conductivity of composites, while dielectric fillers effectively dissipate heat and simultaneously provide electrical insulation. Moreover, the mechanisms of heat transfer, such as phonon and electron transport and interfacial resistance, are explained. Finally, the article highlights the potential applications of such composites in electronics, energy, automotive, and aerospace industries.